Rural–urban disparity in community-based health insurance enrollment in Ethiopia: a multivariate decomposition analysis using Ethiopian Mini Demographic Health Survey 2019 - Tsega, Yawkal; Alemu, Hiwot Tadesse; Geberu, Demiss Mulatu; Hagos, Asebe; Jejaw, Melak; Abera, Kaleab Mesfin; Tiruneh, Misganaw Guadie; Demissie, Kaleb Assegid; Asmare, Lakew; Endawkie, Abel; Negash, Wubshet Debebe; Workie, Amare Mesfin; et al. (Frontiers in Public Health, 2024)
Background: In Sub-Saharan Africa, achieving Universal Health Coverage (UHC) and protecting populations from health-related financial hardship remains a challenging agenda. Subsequently, Community-Based Health Insurance (CBHI) has gained interest in low and middle-income countries, like Ethiopia. However, the rural-urban disparity in CBHI enrollment has not yet been well investigated using multivariate decomposition analysis. Therefore, this study aimed to assess the Rural-Urban Disparity of CBHI enrollment in Ethiopia using the Ethiopian Mini Demographic Health Survey 2019 (EMDHS 2019).Methods: This study used the latest EMDHS 2019 dataset. The STATA version 17.0 software was used for analyses. Chi-square test was employed to assess the association between CBHI enrollment and the explanatory variables. Rural-urban disparity of CBHI enrollment was assessed using logit-based multivariate decomposition analysis. A p-value of <0.05 with a 95% confidence interval was used to declare the statistical significance.The study found that there was a significant disparity in CBHI enrollment between urban and rural households (p<0.001). About 36.98% of CBHI enrollment disparities were attributed to the compositional (endowment) differences of household characteristics between urban and rural households, and 63.02% of the disparities were due to the effect of these characteristics (coefficients). The study identified that the age and education of the household head, family size, number of under-five children, administrative regions, and wealth status were significant contributing factors for the disparity due to compositional differences between urban and rural households. The region was the significant factor that contributed to the rural-urban disparity of CBHI enrollment due to the effect of household characteristics.There was significant urban-rural disparities in CBHI enrollment in Ethiopia. Factors such as household head age and education, family size, number of under-five children, region of the household, and wealth status of the household contributed to the disparities attributed to the endowment, and region of the household was the contributing factor for the disparities due to the effect of household characteristics. Therefore, the concerned body should design strategies to enhance equitable CBHI enrollment of urban and rural households.